Tes Toleransi Glukosa Oral Pada Ibu Hamil Trimester II Dan III diPuskesmas Rawat Inap Kemiling Bandar Lampung - Mutia Hoirunnisah; Fonda Octarianingsih; Festy Ladyani; Bambang Kurniawan (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
This study aims to determine the description of an oral glucose tolerance test (TTGO) in second and third trimester pregnant women in Puskesmas Inpatient Kemiling Bandar Lampung in 2019-2020. This type of research is descriptive qualitative. The sample in this study used a total sampling technique and obtained a total sample of 30 respondents. TTGO results are known for all pregnant women trimester II and trimester III with the results of the highest glucose levels in the second trimester is 101-110 mg/dl 7 respondents (46.7%), in the third trimester that is 70-90 mg/dl 5 respondents (33, 3%), having age <35 years as many as 12 respondents (80%) and 12 respondents (80%). BMI normal trimester II 7 respondents (46.7%), whereas in the third trimester were overweight 9 respondents (60%). The most parity history of pregnant women was primipara in the second trimester 6 respondents (40.0%) and third trimester 7 respondents (46.7%), did not have a history of abortion trimester II 12 respondents (80%) and 13 respondents (86.7%) trimester III. There is no history of second-trimester macrosomia infants 15 respondents (100%) and third trimester 14 respondents (93.3%). No family history of diabetes was found, a history of gestational diabetes and blood pressure <140/90 in the second and third trimester pregnant women were 15 respondents (100%). TTGO can conclude data about a person's risk of having diabetes or already having diabetes mellitus